COMPUTATIONALLY TARGETING MALARIA DRUG TARGET PROTEIN PLASMEPSIN II USING NEEM SECONDARY MEATBOLITES - LAVANYA GUNAMALAI; D.VANILA (International Journal of Pharma and Bio Sciences, 2015)
Vector borne diseases become very common in India especially, the malarial diseases caused by parasites. In this current study, we have retrieved the neem metabolites from pubchem database to target against a drug target protein PDB-1LF2, Plasmepsin II for malarial disease using computational biology techniques. The dock score and interaction amino acid residue of plasmepsin II with isomargololone shows 19.04 Kcal/mol at residues ASP34, myrictinin is 33.29 Kcal/mol at residues THR217, ASP34. Morgolonone shows a dock score of 13.29 Kcal/mol at residues THR217, morgolone is 9.35 Kcal/mol at residues THR21, meldenin is 42.71Kcal/mol at residues THR21. In addition, we compared with standard drug halofantrine, its docked results gives dock score of 31.16 Kcal/mol interacting at residues A: THR217.Meldenin shows the high dock score than the myrictin but the interaction with aspartic acid residue was observed only in myrictin and isomargololone. Hence, further in-vitro and in-vivo studies were need to be carried to confirm the efficiency of these three compounds against malaria